Application of psychomotor reeducation method in the treatment of developmental verbal dyspraxia - Tomić Katarina N.; Marković Ana (TIMS: Acta, 2015)
Dyspraxia is often defined as a disorder or immaturity in the development of motor skills and organized, voluntary movements in the objective space. Considering speech as a motor activity of high specificity and complexity, dyspraxic disorders can also affect the control of oral-buccal-lingual movements and produce problems in oral expression. Developmental verbal dyspraxia is the developmental speech and language disorder that is manifested in the difficulty of programming sequential speech movements, and therefore the production of meaningful verbal messages and its accompanying nonverbal elements. It is diagnosed if the child has no detected peripheral organ damage, severe sensory disturbances, nor muscle weakness or dysfunction. Also, an intellectual functioning is within normal range ande receptive language skills are intact. Good results in the treatment of developmental dyspraxic disorders are achieved by using techniques of psychomotor reeducation method, a kind of developmental therapy that achieves reintegration of practognostical skills and psychomotor activity by using speech, body movements and tonic dialogue as authentic means of communication. This paper will describe certain types of exercises of general psychomotor re-education which can be used in the treatment of developmental verbal dyspraxia, as a supplement to speech and neuropsychological therapy.